PERAN PEMBELAJARAN TARI TRADISIONAL DALAM PENGUATAN NILAI-NILAI KARAKTER SISWA SEKOLAH MENENGAH ATAS (SMA): TINJAUAN LITERATUR SISTEMATIS - Sonia, Uthi; Gustina Putri, Resha; Safhira, Elsa; Astuti, Fuji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education has become a central concern in contemporary schools as globalization, digital media exposure, and shifting social values increasingly shape adolescents' behavior. Traditional dance learning, as part of cultural arts education, offers a promising yet underexplored pathway for strengthening students' character values, particularly at the senior high school level, where identity formation and social orientation are highly prominent. This article presents a systematic literature review examining how traditional dance learning contributes to the development of character values among senior high school students. Sources were identified through academic search engines and repositories, including Google Scholar, Garuda (Garba Rujukan Digital), ResearchGate, ScienceDirect, Taylor & Francis Online, and PubMed Central, using both Indonesian and English keywords related to traditional dance, character education, and senior high school arts learning. Twenty-two empirical and conceptual sources published primarily between 2020 and 2026, supplemented by five foundational theoretical works, were selected and synthesized thematically. The review found that traditional dance learning is consistently associated with the development of discipline, responsibility, cooperation, self-confidence, respect, tolerance, and cultural awareness. However, the findings also reveal important nuances, as dance learning may become a source of performance-related stress when not pedagogically managed effectively. Furthermore, this review identifies significant research gaps, particularly the limited number of studies examining traditional dance within the formal senior high school Cultural Arts curriculum under the Merdeka Curriculum framework and the Pancasila Student Profile, as most existing studies focus on elementary and junior secondary education or extracurricular settings. The article concludes with practical implications for senior high school educators and recommendations for future empirical research.